Glossary of Key Terms in Evaluation and Results Based Management - OECD (OECD, 2009)

The road to results: designing and conducting effective development evaluations - Imas, Morra; G, Linda; Rist, Ray C. (The World Bank, 2009)
The analytical, conceptual, and political framework of development is changing dramatically. The new development agenda calls for broader understandings of sectors, countries, development strategies, and policies. It emphasizes learning and continuous feedback at all phases of the development cycle. As the development agenda grows in scope and complexity, development evaluation follows suit. Development evaluator are moving away from traditional implementation and output-focused evaluation models toward results-based evaluation models, as the development community calls for results and embraces the millennium development goals. As the development community shifts its focus away from projects in order to comprehensively address country challenges, development evaluators are seeking methods with which to assess results at the country, sector, theme, policy, and even global levels. As the development community recognizes the importance of not only a comprehensive but also a coordinated approach to developing country challenges and emphasizes partnerships, development evaluators are increasingly engaged in joint evaluations. These joint evaluations, while advantageous in many respects, add to the complexity of development evaluation (OECD 2006). Additionally, development evaluators increasingly face the measurement challenge of determining the performance of an individual development organization in this broader context and of identifying its contribution. This text is intended as a tool for use in building development evaluation capacity. It aims to help development evaluators think about and explore the new evaluation architecture and especially to design and conduct evaluations that focus on results in meeting the challenges of development.